2020
DOI: 10.1016/j.celrep.2020.108186
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Viral Control by Cytotoxic Lymphocytes Ensures Optimal Adaptive NK Cell Responses

Abstract: SUMMARY Natural killer (NK) cells play a critical role in controlling viral infections, coordinating the response of innate and adaptive immune systems. They also possess certain features of adaptive lymphocytes, such as undergoing clonal proliferation. However, it is not known whether this adaptive NK cell response can be modulated by other lymphocytes during viral exposure. Here, we show that the clonal expansion of NK cells during mouse cytomegalovirus infection is severely blunted in the absence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Studies in mice presented by Dr Joseph Sun showed that the activating receptor Ly49H is expressed on NK cells and binds with high specificity to the mouse cytomegalovirus (MCMV)-encoded glycoprotein m157, which is expressed on infected cells to drive the expansion of virus-specific NK cells during the acute phase of MCMV infection. This proliferation of NK cells depended on the presence of CD8 + T cells 18 . The dependence of NK cell expansion and memory on adaptive immune cells points to another potential pathway for exploring SVEs -namely the potential effect of live vaccines, which are known to initiate adaptive immune responses, on NK cell memory and function.…”
Section: Indications For Sves Within Innate Immunitymentioning
confidence: 94%
“…Studies in mice presented by Dr Joseph Sun showed that the activating receptor Ly49H is expressed on NK cells and binds with high specificity to the mouse cytomegalovirus (MCMV)-encoded glycoprotein m157, which is expressed on infected cells to drive the expansion of virus-specific NK cells during the acute phase of MCMV infection. This proliferation of NK cells depended on the presence of CD8 + T cells 18 . The dependence of NK cell expansion and memory on adaptive immune cells points to another potential pathway for exploring SVEs -namely the potential effect of live vaccines, which are known to initiate adaptive immune responses, on NK cell memory and function.…”
Section: Indications For Sves Within Innate Immunitymentioning
confidence: 94%